Increasing complexity as a challenge for contemporary organizations = Narastająca złożoność jako wyzwanie dla współczesnych organizacji - Osbert-Pociecha, Grażyna (Zielona Góra: Faculty of Economics and Management Press)
In the article, which is literature review highlighted the phenomenon of increasing of complexity in organization. It was presented the prerequisites and implications of the rising complexity. There was indicated also of need for action to reduce the complexity (of both the strategic and operational dimensions of the organization). The most important conclusions are following:
Keywords: Complexity of the organization; Focus on simplicity; Less give more; Złożoność organizacji; Orientacja na prostotę; "Mniej daje więcej"